Miriam Hopkins : life and films of a Hollywood rebel - Ellenberger, Allan R., 1956- (Screen classics., 2018)
"In the first comprehensive biography of this colorful performer, Allan R. Ellenberger illuminates Hopkins's fascinating life and legacy. Her freewheeling film career was exceptional in studio-era Hollywood, and she managed to establish herself as a top star at Paramount, RKO, Goldwyn, and Warner Bros. Over the course of five decades, Hopkins appeared in thirty-six films, forty stage plays, and countless radio programs. Later, she emerged as a pioneer of TV drama. Ellenberger also explores Hopkins's private life, including her relationships with such intellectuals as Theodore Dreiser, Dorothy Parker, Gertrude Stein, and Tennessee Williams"--